Unraveling the Riddle of President Joko Widodo's Speech Abbreviations and Its Translation into Arabic. - Ahmad Salah; Fathur Rokhman; Hari Bakti Mardikantoro; Imam Baehaqie (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The use of abbreviations and acronyms is a common phenomenon in the Indonesian language that has developed since the 1960s, particularly in military contexts. This usage has spread to various fields such as social, political, economic, cultural, and religious areas, making it an essential part of everyday communication in Indonesia. However, excessive and inconsistent abbreviation often leads to confusion. The Arabic language also has abbreviations and acronyms, but their number is far from fewer compared to Indonesian. The main challenge in translating abbreviations from Indonesian to Arabic lies in the differing characteristics of abbreviation formation between the two languages. Abbreviations in Arabic are generally based on root words or specific prefixes, which makes them different from the more flexible abbreviations in Indonesian. This study examines the challenges of translating abbreviations and acronyms in the official speeches of Indonesian President Joko Widodo from Indonesian to Arabic. Data shows that around 40% of translation errors in official speeches are due to incorrect translation of abbreviations and acronyms. A survey of specialized translators reveals that approximately 78% of them face difficulties in translating abbreviations and acronyms from Indonesian to Arabic. This study employs a qualitative method with a descriptive approach to understand and address the challenges in translating abbreviations and acronyms from Indonesian to Arabic.